Clinical Characteristics of Ocular Sarcoidosis: A Population-Based Study 1976–2013. (3rd April 2019) - Ungprasert, Patompong; Tooley, Andrea A.; Crowson, Cynthia S.; Matteson, Eric L.; Smith, Wendy M.
ABSTRACT: Purpose : To characterize the epidemiology and clinical characteristics of ocular involvement in patients with systemic sarcoidosis. Methods : An inception cohort of patients with systemic sarcoidosis in 1976–2013 in Olmsted County, Minnesota, was identified based on comprehensive individual medical record review. Medical records of those patients were then reviewed for ocular involvement. Results : A total of 345 incident cases of systemic sarcoidosis were identified. Ocular involvement occurred in 23 patients (7%). The most common ocular disease was uveitis (61%) followed by dry eye disease, conjunctival nodule, episcleritis, anterior scleritis, and conjunctivitis. Anterior uveitis was the most common type of uveitis (71%). The visual outcome of uveitis was favorable with only one patient lost three or more lines of VA during follow-up and had VA of less than 20/200 at last visit. Conclusion : Ocular involvement occurred in 7% of sarcoidosis patients. Uveitis was the most common type of ocular disease.